A Survey of Green Burial Sites in England and Wales and an Assessment of the Feasibility of a Groundwater Vulnerability Tool - Kim, Kye-Hoon; Hall, Mark L.; Hart, A.; Pollard, Simon J. T. (Taylor & Francis, 2008)
Since 1994, 200 'green' or natural burial sites have been developed in the UK and Eire, attracting regulatory attention because of perceived risks to groundwater. Here, a survey of natural burial practice in England and Wales (n=49 of 141 elicited) is presented, providing data on operational trends and supporting the design of a groundwater vulnerability assessment tool. Natural burial grounds are generally small in area (< 0.8 ha), adopt a mean single burial depth of 1.45 m bgl and a mean plot density of ca. 1480 graves ha-1. A vulnerability screening tool is described that allows a desk-based evaluation of sites by reference to seven groundwater risk attributes. Initial feasibility is evaluated through application to 131 sites.
Keywords: Cemetery; groundwater; pollution; natural burial grounds; risk; vulnerability